The Effect of Parental Socio-Economy on Students' English Achievement - Nikmatul Fitriah (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2021)
The purpose of this study was to figure out the effect of the socio-economic status of parents on students’ English achievement. The research design of this study was ex-post facto research. The participants were the first grade of MA Bilingual Batu and took 30 students as the samples. The instruments of the research were the questionnaire and the midterm test score. The data were analyzed using IBM SPSS version 20 with using independent sample t-test. The mean score of students with high socioeconomic status was 61.36 and 51.14 for students with the low socio-economic status of parents. The data showed that the significant value was 0.002 which means there was a significant different between socio-economic status of parents and students’ English achievement.